A Behavior-Analytic View on Nudges: Individual, Technique, and Ethics. - da Rocha, César Antonio Alves; Hunziker, Maria Helena Leite (Behavior & Social Issues, 2020)
Behavior analysis and behavioral economics represent different traditions, but with relevant points of intersection and complementarity. Recent studies point to convergences and divergences, often in a nonspecific way, and thus lack a careful analysis of some ontological, technical, and ethical aspects—particularly those involved in proposals of such sciences for the regulation of life in society. This article aims to elucidate points of contact and distancing between these sciences, focusing on the concept of nudge. A behavior-analytic view on the concept of nudge is provided with a focus on (a) its underlying view of the individual, (b) a sample of nudging techniques, and (c) some of the ethical arguments of its proponents. It is suggested that although interchanges between behavior analysis and behavioral economics are feasible and promising, there are significant differences between their theoretical foundations. Finally, how the dialogue between both could lead to a reconsideration of the centrality of some of B. F. Skinner's propositions is discussed.